Social and Political Satire in Mark Twain's A Connecticut Yankee in King Arthur's Court - Smejkalová, Markéta (Univerzita Pardubice, 2017)
This bachelor thesis is concerned with the political and social satire portrayed in Mark Twain's A Connecticut Yankee in King Arthur's Court. The first part of the thesis explains the term of political and social satire and its use. The second chapter gives a brief insight into the life of the author, along with his ideals and opinions. The analysis of the book's criticism is covered in the third part of the paper. In this part, there is an overview of the different opinions of critics concerning what the focus of the book's criticism is, followed by a description of the main characters and the analysis of the concrete examples of the political and social satire in the novel. The fourth chapter covers the summary of my research in the conclusion of the thesis.
Sociální a politická satira v knize Yankee z Connecticutu na dvoře krále Artuše od Marka Twaina
Keywords: Twain; satire; politics; society; history; present; Twain; satira; politika; společnost; historie; současnost